2016
DOI: 10.1016/j.childyouth.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Use of evidence-based interventions in child welfare: Do attitudes matter?

Abstract: Implementation of evidence-based programs in progressed slowly, with the majority of services in child welfare settings lacking empirical evidence for effectiveness. In other settings, research has identified providers’ attitudes about evidence-based practices (EBPs) as a potential barrier to adoption of EBPs. As little research has focused on the role of attitudes in influencing use after training in an EBP in child welfare, the potential for attitudes to impede implementation efforts in child welfare is uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
1
12
2
Order By: Relevance
“…In support of this idea, this study appears to be among the only ones to nd positive changes over time in practitioners' attitudes and training needs towards EBPs. Contrary to the present study, no structured implementation strategy was put in place to support practitioners following their EBP training in the other studies (22,23). The authors had suggested that this may be a reason why there was no change in practitioners' perceptions over time.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In support of this idea, this study appears to be among the only ones to nd positive changes over time in practitioners' attitudes and training needs towards EBPs. Contrary to the present study, no structured implementation strategy was put in place to support practitioners following their EBP training in the other studies (22,23). The authors had suggested that this may be a reason why there was no change in practitioners' perceptions over time.…”
Section: Discussioncontrasting
confidence: 69%
“…Regarding attitudes, Lim et al (14) observed an increase in the appeal of EBPs as perceived by community mental health practitioners immediately following their participation in three workshops on evidence-based techniques intended to decrease internalizing and externalizing problems among youths. Another study involving ve measures over a 14-month period yielded different results, with no changes in attitudes towards EBPs being observed among practitioners in the child welfare sector who received training in an evidence-based parenting program (22). However, as pointed out by the authors of this study, the study context did not involve a "full implementation strategy."…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In support of this idea, this study appears to be among the only ones to nd positive changes over time in practitioners' attitudes and training needs towards EBPs. Contrary to the present study, no structured implementation strategy was put in place to support practitioners following their EBP training in the other studies (22,23). The authors had suggested that this may be a reason why there was no change in practitioners' perceptions over time.…”
Section: Discussioncontrasting
confidence: 67%
“…Regarding attitudes, Lim et al (14) observed an increase in the appeal of EBPs as perceived by community mental health practitioners immediately following their participation in three workshops on evidence-based techniques intended to decrease internalizing and externalizing problems among youths. Another study involving ve measures over a 14-month period yielded different results, with no changes in attitudes towards EBPs being observed among practitioners in the child welfare sector who received training in an evidence-based parenting program (23). However, as pointed out by the authors of this study, the study context did not involve a "full implementation strategy."…”
Section: Introductionmentioning
confidence: 73%